Asbestos induced diffuse pleural fibrosis: pathology and mineralogy. Issue 8 (August 1987) - Stephens, M; Gibbs, A R; Pooley, F D; Wagner, J C
Abstract : Lungs from seven cases of diffuse pleural fibrosis with known asbestos exposure were studied to determine the gross and microscopic pathological features and relate these to the analysed mineral fibre content of the lung. All seven individuals had had substantial exposure, ranging from two to 25 years, and chronic chest problems and at necropsy all cases met the criteria for compensatable disease. Macroscopically, all had extensive visceral pleural fibrosis and extensive areas of adhesions, and four also had discrete parietal pleural plaques. The histological features were similar in all the cases--most strikingly the basket weave pattern of the thickened pleura and a dense subpleural parenchymal interstitial fibrosis with fine honeycombing, extending up to 1 cm into the underlying lung. The similar histological appearances raise the possibility that diffuse pleural fibrosis and pleural plaques have a similar pathogenesis. Amphibole asbestos (crocidolite and amosite) counts were high in six of the seven cases and chrysotile counts in four; four cases had high mullite counts, but the importance of this is not known. It is concluded that diffuse pleural fibrosis is a specific asbestos associated entity, of uncertain pathogenesis, with mineral fibre counts falling between those found with plaques and those in minimal asbestosis.